1568 Seasonal changes of physiological responses associated with heat acclimatisation. (24th April 2018) - Tabuchi, Shota; Kawanami, Shoko; Inoue, Daisuke; Morizane, Shuhei; Inoue, Jinro; Horie, Seichi
Abstract : Introduction: It is known that heat stroke is likely to occur when workers are not acclimatised to heat. The purpose of this study is to clarify if the physiological responses of heat acclimatisation are different by the seasonal difference of the temperature in living environment. Methods: Four healthy males in twenties repeated a 20 minutes-exercise on an ergometer at 40% VO2 max for three times in three different thermal environments in the artificial climate room controlled at 28°C, then elevated to 34°C and finally to 40°C where relative humidity was fixed at 50%. Each exercise was followed by 20 minutes-rest period kept seated in the adjunct room at 24°C. They were asked to exercise consecutively for five days. This series of intervention was repeated during summer and winter seasons. We continuously measured their auditory canal temperature ( t ac ) and heart rate (HR). We also examined their sweat Na + and K + concentration and estimated their sweat volume from the body weight loss. Result: The observed t ac and HR at the end of the exercise were generally higher in winter compared to summer. The sweat volume gradually increased for five days and the volume during the first exercise period at 28°C was larger in summer; however, the amount of increase was larger in winter. The sweat Na + concentration positively correlated with sweat volume and we observed smaller elevation of Na + concentration along with the increase of sweat volume in summer. Discussion: The lower t ac and HR, earlier sweating, and smaller elevation of Na + concentration during heat acclimatisation in summer seem to be caused by the different thermal condition of living environment